Drag each equivalent expression to the box where it belongs. Some expressions may not belong in either box.

Yes:


-3(4x + 12)
-4(3x -9)
4(2x - 6)
-4(-2x - 6)
3(-4x +12)
2(4x - 12)
-12x + 36
8x - 24
No:

Respuesta :

Assuming your target boxes are (-12x +36) and (8x -24), here are the classifications of the expressions with parentheses.

-3(4x + 12) = -12x -36 (neither)

-4(3x -9) = -12x +36

4(2x - 6) = 8x -24

-4(-2x - 6) = 8x +24 (neither)

3(-4x +12) = -12x +36

2(4x - 12) = 8x -24

_____

The distributive property applies:

... a(b+c) = ab +ac

Same signs multiply to give positive. Different signs multiply to give negative.

ACCESS MORE